Protection of Whistleblowers in the Workplace. Who Is Protected and Who Is Responsible under the Provisions of the EU Directive 2019/1937? - Hajn, Zbigniew (Towards a Better Protection of Workplace Whistleblowers in the Visegrad Countries, France and Slovenia, 2021)
The aim of this chapter is to present selected problems related to the transposition intonational law of the provisions of the Directive (EU) 2019/1937 which define the personalscope of its application. The author focuses on the prerequisites for recognising a givenperson as a whistleblower (reporting person) and including them in the circle of protectedpersons. Among other things, he considers issues related to the Directive’s departure fromthe recognition of acting in good faith and in the public interest as conditions for the protectionof a whistleblower, as well as the relevance for the protection of a whistleblower ofthe obligation to report breaches existing in some national laws. He also argues that therelationship that whistleblowers enter into with the organisation affected by the whistleblowing,referred to in the English version as a “work-based relationship”, cannot be equated, asother language versions do, with an employment relationship. The author also proposes,following earlier postulates, to extend the personal scope of protection of facilitators. Healso attempts to clarify the notion of “legal entity” as the main entity responsible for thecreation and functioning of internal channels. He further postulates more complete regulationin national legislation of the rules of liability of entities responsible for fulfilling theobligations imposed by the Directive.